Re-expression of the p53 Gene by Inhibiting the Mdm-2 Receptor in Wild-type p53 Tumors for the Treatment of Glioblastoma: A Mini Review - Ahmed, Syed Ijlal (Cureus, 2018)
Glioblastoma multiforme (GBM) has been the topic of immense research in recent years. The suitable therapeutic approach towards this wild-type p53 tumor has been the topic of ongoing discussion for some decades now. There has been a substantial debate about the role of mouse double minute-2 (MDM-2) antagonists in the treatment of GBM recently. We have reviewed the current data in our study to establish the consensus about recent interventions. Our review of the literature suggests that MDM-2 antagonists are currently a more suitable approach with improved efficacy, and it might be utilized in the future for significant results. Newer analogs of MDM-2 antagonists with better pharmacokinetics profiles and the least drug-drug interactions were also discussed in our research. It was concluded that MDM-2 antagonists are improved therapy against GBM but evidential proof with more experimental studies is needed to standardize this therapy in near future.